Gender Equality and Labor Market Participation : Evidence from Scandinavian Countries - Ahmad Zainur Rofikin; Khosim Sukrisno; Petrus Rudolf Mayore (Global Economics: International Journal of Economic, Social and Development Sciences, 2024)
This paper analyzes the progress of gender equality in labor markets across Scandinavian countries and its economic implications. By comparing labor force participation rates, wage gaps, and social policies, the study identifies factors contributing to higher gender parity. Results show that robust parental leave systems and flexible working arrangements significantly enhance women's participation. The findings underscore the importance of supportive policies in achieving economic inclusivity.